PhD Defence: â€œIranian Community Media in Stockholm: Locality, Transnationality, and Multicultural Adaptationâ€ by Daniel Ahadi - Phan, Vu Thuy Anh (Stream: Interdisciplinary Journal of Communication, 2016)
<!--[if gte mso 9]> <![endif]--> <!--[if gte mso 9]> Normal 0 false false false RU X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:Cambria; mso-ansi-language:EN-CA;} --> <!--[endif] --> <!--StartFragment--> <span style="font-family: Cambria; background-image: initial; background-attachment: initial; background-size: initial; background-origin: initial; background-clip: initial; background-position: initial; background-repeat: initial;" lang="EN-GB">Our dear colleague, <span style="font-family: Cambria; background-image: initial; background-attachment: initial; background-size: initial; background-origin: initial; background-clip: initial; background-position: initial; background-repeat: initial;" lang="EN-GB">Daniel Ahadi<span style="font-family: Cambria; background-image: initial; background-attachment: initial; background-size: initial; background-origin: initial; background-clip: initial; background-position: initial; background-repeat: initial;" lang="EN-GB">, will defend his PhD Dissertation on Monday, June 27, 2016 <span style="font-family: Cambria; background-image: initial; background-attachment: initial; background-size: initial; background-origin: initial; background-clip: initial; background-position: initial; background-repeat: initial;" lang="EN-GB">at Harbour Centre, Library Thesis Room, Bennett Library Room 2020, <span style="font-family: Cambria; background-image: initial; background-attachment: initial; background-size: initial; background-origin: initial; background-clip: initial; background-position: initial; background-repeat: initial;" lang="EN-GB">(10:30 am - 1:30 pm). Here is the abstract of his dissertation “Iranian Community Media in Stockholm<span style="font-family: Cambria; background-image: initial; background-attachment: initial; background-size: initial; background-origin: initial; background-clip: initial; background-position: initial; background-repeat: initial;" lang="EN-GB">”. <!--[if gte mso 9]> <![endif]--> <!--[if gte mso 9]> Normal 0 false false false RU X-NONE X-NONE <![endif]--><!--[if gte mso 9]>